2020
DOI: 10.3390/pr8050576
|View full text |Cite
|
Sign up to set email alerts
|

Business Models for Carbon Capture, Utilization and Storage Technologies in the Steel Sector: A Qualitative Multi-Method Study

Abstract: Carbon capture, utilization, and storage (CCUS) is a combination of technologies capable of achieving large-scale reductions in carbon dioxide emissions across a variety of industries. Its application to date has however been mostly limited to the power sector, despite emissions from other industrial sectors accounting for around 30% of global anthropogenic CO2 emissions. This paper explores the challenges of and requirements for implementing CCUS in non-power industrial sectors in general, and in the steel se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 101 publications
(84 reference statements)
0
8
0
Order By: Relevance
“…In this regard, the literature has explored strategies, business management tools and frameworks that have the purpose of achieving a sustainable planning process and reaching the market. Specifically, studies have been undertaken to evaluate and identify optimal management practices in TT in the construction industry (Alwan et al, 2017;Muslemani et al, 2020;Shakeel et al, 2017;Suprun et al, 2019;Li, 2018a, 2018b).…”
Section: Tt Strategies Tools and Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, the literature has explored strategies, business management tools and frameworks that have the purpose of achieving a sustainable planning process and reaching the market. Specifically, studies have been undertaken to evaluate and identify optimal management practices in TT in the construction industry (Alwan et al, 2017;Muslemani et al, 2020;Shakeel et al, 2017;Suprun et al, 2019;Li, 2018a, 2018b).…”
Section: Tt Strategies Tools and Frameworkmentioning
confidence: 99%
“…Through this case study, ineffective strategies, policies and leadership were highlighted, which have prevented the full exploitation towards sustainable production. Next, by exploring the theoretical underpinnings of lowcarbon technology business models and through semi-structured interviews with industry experts and academics,Muslemani et al (2020) point to revenue as the central element in creating value for these business models. However, despite the promising potential of low-carbon technologies for energy efficiency in the construction sector, the lack of a viable business model has deterred the commercialisation of these technologies developed within universities(Muslemani et al, 2020) Shakeel et al (2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although a number of industry-focused studies (e.g. Element Energy, 2018; Muslemani et al, 2020) have suggested that the creation of a green steel product market may be a viable means of creating a revenue stream to support greener steel production, key questions remain, including: 1) what would a 'green' steel product actually be? 2) how could governments support the creation of markets for such products?…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Various processes have been established for the capture and storage of CO 2 , resulting in the reduction of its concentration in the atmosphere [11][12][13][14][15][16]. The capture technique requires the separation of CO 2 from other gases at a high pressure followed by its adsorption [17].…”
Section: Introductionmentioning
confidence: 99%